Pengujian Black Box pada Aplikasi Keamanan Data Multimedia Message Service (MMS) Berbasis Android Menggunakan Teknik Equivalence Partitions - Abdul Aziz (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Currently, almost everyone has used electronic devices in which there are applications that have been installed. To meet user satisfaction, this application must go through a testing process to check all errors in the system so that they can be fixed later. This test is performed on a previously created Data Security Application. Software testing that has been done is using the Black Box method with the Equivalence Partition technique. From the test results, it was found that cases that need to be fixed are the fields in the Create Message Form.